Discrete Redox Signaling Pathways Regulate Photosynthetic Light-Harvesting and Chloroplast Gene Transcription - Allen, John F.; Santabarbara, Stefano; Allen, Carol A.; Puthiyaveetil, Sujith (PLOS ONE, 2011)
In photosynthesis in chloroplasts, two related regulatory processes balance the actions of photosystems I and II. These processes are short-term, post-translational redistribution of light-harvesting capacity, and long-term adjustment of photosystem stoichiometry initiated by control of chloroplast DNA transcription. Both responses are initiated by changes in the redox state of the electron carrier, plastoquinone, which connects the two photosystems. Chloroplast Sensor Kinase (CSK) is a regulator of transcription of chloroplast genes for reaction centres of the two photosystems, and a sensor of plastoquinone redox state. We asked whether CSK is also involved in regulation of absorbed light energy distribution by phosphorylation of light-harvesting complex II (LHC II). Chloroplast thylakoid membranes isolated from a CSK T-DNA insertion mutant and from wild-type Arabidopsis thaliana exhibit similar light- and redox-induced 32P-labelling of LHC II and changes in 77 K chlorophyll fluorescence emission spectra, while room-temperature chlorophyll fluorescence emission transients from Arabidopsis leaves are perturbed by inactivation of CSK. The results indicate indirect, pleiotropic effects of reaction centre gene transcription on regulation of photosynthetic light-harvesting in vivo. A single, direct redox signal is transmitted separately to discrete transcriptional and post-translational branches of an integrated cytoplasmic regulatory system.